Magnetic Resonance Imaging in Traumatic Brachial Plexus Injuries: A 6-Year Experience. - Clarissa Gadelha Maia Vieira,MD; Cláudio Régis Sampaio Silveira, MD; Brenda Machado Pereira,MD; Ingrid Carvalho de Holanda,MD; Ariana Sorah Serra dos Santos Jacinto,MD; Francisco Flávio Leitão de Carvalho Filho, MD; Daniel Gurgel Fernandes Távora, MD; Avneesh Chhabra, MD (British Journal of Healthcare and Medical Research, 2023)
Background and Purpose: There is limited information in the literature on epidemiology of high-energy brachial plexus injuries evaluated with MR neurography (MRN). The aim of the present study is to describe the demographic characteristics of brachial plexus injuries secondary to motorcycle accident patients in the city of Fortaleza-Ceara, Brazil, and analyze the association of those data with the features of the brachial plexus lesions observed on MRN findings. Materials and Methods: A review of sixty medical charts and MRN findings of victims of motor vehicle accidents (MVA) in northeast, from November 2011 to November 2017. Demographic and imaging data collected included age, sex, laterality and level of the lesion and time interval between trauma and MRN examination. The MRN examinations were carried out on a GE 1.5T MR unit (Signa HDxT- General Electric, Milwaukee, USA) or on a Phillips 3T MR unit (Philips Achieva X-series - Philips Medical Systems, Best, The Netherlands). Dedicated multichannel phased-array coils. Results: The longest time interval from trauma to imaging was 330 days and between trauma and surgery was 692 days. Preganglionic lesions (avulsion) predominated, consisting of 52 patients (86.6%) reflecting the high energy trauma with upper limb traction from the neck. The lesions were most prevalent at the C6-C8 levels. Pseudomeningocele was identified in 62.9% of the preganglionic lesions and in only 1.6% of the postganglionic lesions. Regional muscle denervation changes were seen in all pre-ganglionic injuries and most of post-ganglionic injuries. Conclusions: MRN of the brachial plexus provides important insights into the distribution of neuromuscular lesions in high energy MVA trauma and these findings enrich the literature for researchers and clinicians focused on managing such patients and/or defining prognostic strategies.